2008
DOI: 10.1007/s12224-008-9016-7
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Trivial Relationships: on the Hidden Aspects of Biodiversity

Abstract: The strong correlation found between detailed and simple measures of biodiversity at landscape-scale may suggest that patterns of detailed diversity measures are artifacts (sensu Palmer et al. 2008, this issue). For example the regional pattern of Compositional Diversity (a measure of within-stand structural complexity) can be considered as a correct but trivial result because this pattern is almost completely determined (at least statistically) by the regional pattern of species richness. However, I argue tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…Kalusová et al (2009) have even found that site-related factors explain more from the variance in species abundances than soil parameters even within one region. The response as assessed by the structural descriptors did not depend on species identities, which allows direct comparison even among sites that do not share species at all (Bartha et al 1998;Bartha 2008). This is also reflected in our results with structural vegetation descriptors: site identity did not influence ordination and therefore variance partitioning was actually not necessary.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Kalusová et al (2009) have even found that site-related factors explain more from the variance in species abundances than soil parameters even within one region. The response as assessed by the structural descriptors did not depend on species identities, which allows direct comparison even among sites that do not share species at all (Bartha et al 1998;Bartha 2008). This is also reflected in our results with structural vegetation descriptors: site identity did not influence ordination and therefore variance partitioning was actually not necessary.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, it was exactly bulk density, where larger within-community variation than variation between communities has been observed (Elberling et al 2008). Our results imply that structural differences among stands of the same community, which are often present (Bartha 2008;Virágh et al 2008), can potentially explain such variation.…”
Section: Discussionmentioning
confidence: 57%
“…However, applying null-models based on Monte Carlo randomizations (Gotelli and Graves, 1996;Gotelli, 2001) or mechanistic simulation models Bartha, 2008a) extend this approach for developing spatial statistics dealing with complex non-stationer patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Outcomes of these ecosystem drivers are frequently characterized by macrofauna at recognizable landscape (Fahrig, 2003; Teng et al, 2020; Valladares et al, 2012) and seascape scales (Arias‐Gonzalez et al, 2006; Darling et al, 2019; Oakley‐Cogan et al, 2020; Roff et al, 2019; Staveley et al, 2017; Stuart‐Smith et al, 2018; van Lier et al, 2018). Yet, parameterizing ecosystem drivers of biodiversity from the microhabitat perspective is critical as fine‐scale constraints can generate regional diversity patterns (Bartha, 2008; Bracken & Low, 2012; O'Neill et al, 1989), and amplified degradation through fragmentation and loss of habitat at landscape scales impair community structure, ecosystem functioning, and trophodynamics (Fahrig, 2003; Leal et al, 2014; Tscharntke et al, 2002; Valladares et al, 2012).…”
Section: Introductionmentioning
confidence: 99%